A hypothesis about the radical identity crisis: between the Olivos pact and the experience of the Alliance (1994-2001) (Estudios Sociales, 2022)
This research associates a theoretical dimension -the study of political identities- with an empirical dimension linked to the characteristics of the collective identity of the Radical Civic Union and, in particular, to one of its central aspects, the cleavage between political-administrative honesty and corruption. The hypothesis guiding this research is based on a central assumption: the hyperinflationary crisis of 1989 and the anticipated withdrawal of the Alfonsín government were far from constituting a checkmate to radical identity. The aim is to show that it was, above all, from the Pact of Olivos and the truncated experience of the UCR-FREPASO government, where the keys to the decline of radical identity can be traced; a strong identity that had been anchored for more than a century in the social imaginary of Argentines in correlation with the defense of political democracy and republican honesty.
Keywords: identity; identity crisis; radicalism; Pact of Olivos